2010
DOI: 10.1055/s-0030-1263292
|View full text |Cite
|
Sign up to set email alerts
|

New Insight into an Old Paradigm: Wrapping and Dangling with Lower-Extremity Free Flaps

Abstract: Flap edema can often compromise an otherwise successful lower-extremity microsurgical reconstruction. To train a flap toward maturity, various wrapping and dangling protocols have been described. Mixed tissue oxygenation of a myocutaneous free flap for lower-extremity reconstruction is examined as measured by ViOptix with wrapping and unwrapping during dangling at different postoperative time points. The results are compared with the nonaffected lower extremity and additional healthy controls. Upon dangling a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 14 publications
2
49
1
Order By: Relevance
“…This pattern was modified by the type of flap and duration of training, but it remained fairly constant in its behavior and was well consistent with the findings of Ridgway et al 8 Immediately after the beginning of dependency, an initial increase in StO 2 was noticed in the flap (►Fig. 1).…”
Section: Stosupporting
confidence: 89%
See 2 more Smart Citations
“…This pattern was modified by the type of flap and duration of training, but it remained fairly constant in its behavior and was well consistent with the findings of Ridgway et al 8 Immediately after the beginning of dependency, an initial increase in StO 2 was noticed in the flap (►Fig. 1).…”
Section: Stosupporting
confidence: 89%
“…This state is improved over time as the flaps become independent of the pedicle by vessel ingrowth from the surrounding tissue (randomization) and regain basic innervation. 8,16 However, these effects take place over a longer span of time, while the short-term changes described in this work are more likely attributable to the vascular changes discussed in the following.…”
Section: General Considerationsmentioning
confidence: 75%
See 1 more Smart Citation
“…Cutaneous, subcutaneous, and muscular vascular resistances increase within a limb when venous pressure is greater than 25 mm Hg and decrease blood flow by up to 40%. 8,9 This response to elevated venous pressure is termed the venoarteriolar response. The venoarteriolar response mechanism reportedly continues within tissues even after free-flap transfer.…”
Section: Discussionmentioning
confidence: 99%
“…The venoarteriolar response mechanism reportedly continues within tissues even after free-flap transfer. 6,8,9 Ridgway et al 8 have demonstrated that after dangling for 5 minutes on the seventh postoperative day, tissue oxygenation in a lower-extremity free flap decreases significantly and does not return to the baseline value for as long as 44 minutes. These findings support the common perception of many surgeons, who, therefore, start postoperative mobilization between 1 and 3 weeks after the transfer of free flaps to the lower extremity.…”
Section: Discussionmentioning
confidence: 99%